Growth, Yield and Fruit Quality of Select Vegetables (Tomato, Green Pepper and Garden Eggs) as Affected by “Asase Gyefo” Premium Organic Fertilizer - Ampah, J. (University of Ghana, 2019)
Declining soil fertility has been found to be the main cause of reduction in crop yields. These soils lose their fertility through erosion, leaching and crop removal. Organic fertilizers prepared from human waste has been found to have a greater potential of being used to manage soil fertility and hence increase crop yields. The present study is to determine the nutrients content and effect of Asase Gyefo Organic Fertilizer (AGOF) prepared from human waste on the growth, yield and shelf life of select vegetables (garden eggs, green pepper and tomato). The experiments were laid out in Randomised Complete Block Design (RCBD) using ten treatments namely 5tons/ha AGOF, 7.5 tons/ha AGOF, 10.0 tons/ha AGOF, 12.5 tons/ha AGOF, 15.0 tons/ha AGOF, 17.5 tons/ha AGOF, 20.0/ha tons, 10 tons/ha Poultry Manure, NPK+SA (300kg/ha+150kg/ha) and Control, ran in three replicates. Data collected on the growth were on the 5th, 7th and 9th weeks after sowing. Fruit characteristics, yield and shelf life were also measured at maturity. The results showed that AGOF had all the nutrient elements needed for increased crop production. AGOF applied at 10 tons/ha produced a yield of 2664 kg/ha in garden egg experiment one, which was significantly higher than the yield obtained when the soil was not amended. In green pepper experiments 1 and 2, no significant differences were recorded in the yields. However, in tomato experiment, AGOF applied at 12.5 tons/ha yielded 1543 kg/ha which was significantly higher than 15 tons/ha AGOF and 20 tons/ha AGOF application rates. From the results, AGOF applied at the rate of 12.5 tons/ha gave optimum yield in tomato, while rates of 5 tons/ha of AGOF to 20 tons/ha of AGOF depending on the state of the soil gave the best of growth and yields in green pepper and garden egg test crops, comparable to yields obtained from poultry manure treatment and hence can be used as substitute organic fertilizer for vegetable production.
MPhil. Crop (Horticulture)
Keywords: Fertilizers; Soil Physiochemical Properties; Circular Economy; Ecological Sanitation